2001
DOI: 10.1007/978-3-642-18156-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time RT-PCR for the Detection and Quantification of AML1/MTG8 Fusion Transcripts in Patients with t(8;21) Positive AML

Abstract: AML1/MTG8 was quanti®ed relative to the expression of the GAPDH housekeeping gene by real-time RT-PCR in 22 patients with t(8;21)-positive acute myeloblastic leukaemia (AML) at initial diagnosis and in seven of these patients also during/after chemotherapy and allogeneic bone marrow transplantation. Real-time PCR was able to speci®cally detect and quantify AML1/MTG8 over a 5 log range. The detection limit for t(8;21)-positive cells was a dilution of 1:10 5 . The AML1/MTG8 expression varied considerably among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…186 These promising preliminary data suggest that RQ-PCR is likely to be valuable for MRD monitoring in this subset of AML, with the added advantages that the latter technique is less labor intensive, more reproducible and amenable to standardization lending itself to use in large-scale clinical trials. Preliminary studies of RQ-PCR [42][43][44]187,188 have essentially confirmed the results obtained via competitive RT-PCR, revealing a 3.5-to 20-fold variation in AML1-ETO FG expression levels in diagnostic BM that was not related to blast percentage and which needs to be taken into account when assessing response to therapy. Furthermore, variability in kinetics of response to chemotherapy was noted, and interestingly AML1-ETO transcripts were also detected in patients in long-term remission from AML.…”
Section: Protocols For Rq-pcr Analysis Of Fg Transcripts J Gabert Et Almentioning
confidence: 58%
See 1 more Smart Citation
“…186 These promising preliminary data suggest that RQ-PCR is likely to be valuable for MRD monitoring in this subset of AML, with the added advantages that the latter technique is less labor intensive, more reproducible and amenable to standardization lending itself to use in large-scale clinical trials. Preliminary studies of RQ-PCR [42][43][44]187,188 have essentially confirmed the results obtained via competitive RT-PCR, revealing a 3.5-to 20-fold variation in AML1-ETO FG expression levels in diagnostic BM that was not related to blast percentage and which needs to be taken into account when assessing response to therapy. Furthermore, variability in kinetics of response to chemotherapy was noted, and interestingly AML1-ETO transcripts were also detected in patients in long-term remission from AML.…”
Section: Protocols For Rq-pcr Analysis Of Fg Transcripts J Gabert Et Almentioning
confidence: 58%
“…35,36 There have been numerous manuscripts from individual laboratories demonstrating the reliability of this technology and its potential clinical value for MRD studies using FG transcripts as PCR targets such as BCR-ABL in CML [37][38][39] or ALL, 40 PML-RARA, 41 AML1-ETO [42][43][44] and CBFB-MYH11 45,46 in AML and TEL-AML1 [47][48][49] in ALL patients. However, standardized RQ-PCR procedures are warranted in order to apply this innovative technology for large-scale MRD studies within multicenter therapeutic trials.…”
Section: Introductionmentioning
confidence: 99%
“…In one RQ-RT-PCR study, a rapid increase of the AML1/ETO fusion transcript during CR after BM transplantation was observed, and the patient relapsed 10 weeks later. 35,38 On the other hand, no rapid increase could be seen before relapse by other investigators. 33,36,37 This difference could be because of the fact that only a few data were available from the remission phase before relapse.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, several RQ-RT-PCR studies describe a linear decrease of AML1/ETO for adults in the range of 2-4 log between diagnosis and CR, and some of them remained positive during the ongoing therapy. 23,[33][34][35][36][37] Some children in our study turned from a negative RQ-RT-PCR result to positivity with a low copy number in the next follow-up sample (pts. 2, 5, 12, 13).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation